Wnt3a ligand facilitates autophagy in hippocampal neurons by modulating a novel GSK-3β-AMPK axis - Rios, Juvenal A.; Godoy, Juan A.; Inestrosa, Nibaldo C. (My University, 2018)
Background: In the adult central nervous system (CNS), Wnt signaling regulates dendritic structure and synaptic plasticity. The Wnt signaling pathway can be divided into the canonical (beta-catenin-dependent) and non-canonical pathways. In the canonical pathway, the binding of canonical ligands such as Wnt3a to the Frizzled receptor induces inactivation of glycogen synthase kinase-3 beta (GSK-3 beta), which stabilizes beta-catenin and allows its translocation to the nucleus. However, to date, few studies have focused on beta-catenin-independent Wnt signaling or explained the underlying mechanisms connecting Wnt signaling to cellular energy metabolism. A recent study demonstrated negative regulation of 5' adenosine monophosphate-activated protein kinase (AMPK), a major target of GSK-3 beta that regulates cellular metabolism under diverse conditions. Mainly based on these observations, we evaluated whether Wnt3a ligand modulates autophagy by regulating the GSK-3 beta/AMPK axis. Methods: Cultured primary hippocampal neurons and slices of the CA1 region of rat hippocampus were used. GSK-3 beta inhibition, AMPK activation, PP2Ac expression, and LC3 processing were examined by western blotting. Autophagic compartments were studied using the CYTO-ID (R) fluorescent probe, and mature autophagosomes were observed via transmission electron microscopy (TEM). Results: Wnt3a ligand, acting through the Frizzled receptor, promotes the rapid activation of AMPK by inactivating GSK-3 beta. Biochemical analysis of downstream targets indicated that Wnt3a ligand modulates autophagy in hippocampal neurons. Conclusions: Our results revealed new aspects of Wnt signaling in neuronal metabolism. First, AMPK is an additional target downstream of the Wnt cascade, suggesting a molecular mechanism for the metabolic effects previously observed for Wnt signaling. Second, this mechanism is independent of beta-catenin, suggesting a relevant role for non-genomic activity of the Wnt pathway in cellular metabolism. Finally, these results have new implications regarding the role of Wnt signaling in the modulation of autophagy in neurons, with a possible role in the removal of accumulated intracellular proteins.
Keywords: neuron; wnt signaling; ampk; autophagy; metabolism